A POSIÇÃO PRONA MELHORA A MECÂNICA RESPIRATÓRIA DE NEONATOS EM RESPIRAÇÃO ESPONTÂNEA - Eickhoff, Heloísa M.; Schneider, Ana; Schöffel, Tatiana; Strassburger, Simone Z.; Winkelmann, Eliane R.; Teixeira, Luciana F. (Salão do Conhecimento, 2013)
Resumo